P098 Human protothecosis: Acase report in Northeastern Brazil. (20th September 2022) - De Maria Azevedo, Conceicao; Santos, Daniel Wagner; Diniz, Yankee Costa Magalhaes Yankee Costa Magalhaes; Simões-Neto, Eudes Alves Simões Neto; Mendes, Rafael Bezerra Rafael Bezerra; Diniz, Francy Dazia Menezes Ferreira; Silva, Raimunda Ribeiro; Conceição, Patrícia Cristina Ribeiro; de Oliveira Melo, Bruna; Marques, Sirlei Garcia; Bonfim, Maria Rosa Quaresma
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Introduction: Protothecosis is an emergent disease caused by members of the genus Prototheca. Most such infections probably occurred by traumática inoculation into subcutaneous tissues. Objectives: It is to report a case of human cutaneous protothecosis identified in the state of Maranhão, northeast Brazil. Case report: 75-year-old patient, Merchant, from the municipality of São Luís Island, Northeastern Brazil. He sought care referring to an erythematous and painful lesion on the left arm that started 6 months before the treatment. On examination, he presented an infiltrative, hyperemic lesion with burning pain throughout the upper limb (Fig. 1). The patient reported that a week before the onset of the condition, he suffered trauma on the arm, with a laceration in the skin, while cleaning a sewage system with clay pipes. During the healing process, he noticed a hyperemic, slightly pruritic lesion measuring 2 cm which did not improve. He sought medical assistance at the dermatological service, who suspected dermatophytosis, initiating treatment with terbinafine (250 mg, once a day), evolving with worsening of the lesion. A lesion biopsy was indicated, to histopathological examination, which showed circular, moniliform structures, diagnosed as protothecosis (Fig. 2). Treatment with itraconazole (200 mg/day) was started, with no therapeutic response and the lesion spread throughout the patient's left upper limb. Submitted to a new investigation with biopsy for direct research and culture for fungi, being identified Prototheca Wicherhamii, by Maldi-Tof®, with sensitivity to itraconazole and ampfotericin B. PCR amplification of the genetic material obtained in the clinical isolate was performed with purification of its product, and sequencing showed genetic similarity of 97, 46% with Prototheca Wickerhamii . The sequence obtained was deposited in Genbank under number MZ409514. In the absence of therapeutic response to itraconazole (400 mg/day), and significant worsening of the lesion, with presentation of a secondary infection caused by Staphylococcus haemoliticus, treatment with Clindamycin (900 mg/day for 10 days) and Liposomal Amphotericin B (4 mg/kg/day for 45 days) were performed. After suspension of Liposomal Amphotericin B, the lesions recurred in 15 days, and voriconazole (200 mg 12/12 h) was prescribed for 6 months, with complete regression of the lesions. Currently, he is free of injuries, having been followed up every 6 months. Conclusion: Rare disease caused by chlorophyllous algae may be surprising due to the severity and lack of response to antifungals that show sensitivity in vitro .